Small and Medium Sized Book Publishers in the Contemporary Lithuanian Book Publishing Landscape - Misiūnas, Remigijus (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English]The article was prepared taking into account the false conclusions about the current situation of book publishing in Lithuania, in particular, the activities of small and medium sized publishers. The aim of the article was to select small and medium publishers and to identify the specificity of their activities in contemporary Lithuanian book publishing. This goal implies several objectives: 1. To define what is included in the composition of small and medium-sized publishers and to carry out their statistical analysis in various sections; 2. To analyze the relationship between small and medium-sized publishers with the state; 3. To analyze the influence of the book distribution situation on the activities of small and medium-sized publishers; 4. Find out whether IT development provides new opportunities for small and medium-sized publishers. On the basis of scarce research, media publications, various statistical sources as well as the author’s personal observations of the book publishing situation and networking with the publishers, it has been determined that there are more than 100 book publishers today in Lithuania, of which about 90 are small and medium-sized. An analysis of the existence of a publishing support system in Lithuania has shown that small and medium-size publishers cannot rely on it for their survival and activities because the support system does not take into account the specificity of publishing as a cultural activity and business. A major obstacle to the activities of small and medium-sized publishers is the monopoly on book trading system in Lithuania. Such a system gave rise to unfair competition. As a result, small and medium-sized publishers have to increasingly focus on direct distribution and adjust their publishing plans accordingly. Furthermore, the development of digital book publishing in Lithuania has not justified previous forecasts and failed to become a source of additional revenue for small and medium-sized publishers. Small and medium-sized publishers experience constant instability, they are challenged by the factors they cannot change such as market size, emigration and reduced purchasing power of people. Even though certain challenges are believed to be manageable, no positive changes to improve the publishers’ situation have been introduced so far, such as a clear approach to publishing from the state, improved system of support and a regulation of the monopolized book distribution market. However, small and medium-sized publishers still are and will remain part and parcel of the Lithuanian book publishing landscape. The publishers who exit the market are replaced by new entrants into publishing business, therefore their activities should be evaluated both quantitatively and qualitatively.
Keywords: publisher, small publisher, medium-sized publisher, state support, book distribution, digital publishing